Traditional Japanese medicine Kamikihito ameliorates sucrose preference, chronic inflammation and obesity induced by a high fat diet in middle-aged mice - Maejima, Yuko; Yokota, Shoko; Yamachi, Megumi; Misaka, Shingen; Ono, Tomoyuki; Oizumi, Hiroaki; Mizuno, Keita; Hidema, Shizu; Nishimori, Katsuhiko; Aoyama, Masato; de Wet, Heidi; Shimomura, Kenju (Frontiers in Endocrinology, 2024)
The high prevalence of obesity has become a pressing global public health problem and there exists a strong association between increased BMI and mortality at a BMI of 25 kg/m 2 or higher.The prevalence of obesity is higher among middle-aged adults than among younger groups and the combination of aging and obesity exacerbate systemic inflammation. Increased inflammatory cytokines such as interleukin 6 and tumor necrosis factor alpha (TNF) are hallmarks of obesity, and promote the secretion of hepatic C-reactive protein (CRP) which further induces systematic inflammation. The neuropeptide oxytocin has been shown to have anti-obesity and anti-inflammation effects, and also suppress sweet-tasting carbohydrate consumption in mammals. Previously, we have shown that the Japanese herbal medicine Kamikihito (KKT), which is used to treat neuropsychological stress disorders in Japan, functions as an oxytocin receptors agonist. In the present study, we further investigated the effect of KKT on body weight (BW), food intake, inflammation, and sweet preferences in middle-aged obese mice. KKT oral administration for 12 days decreased the expression of proinflammatory cytokines in the liver, and the plasma CRP and TNF levels in obese mice.The effect of KKT administration was found to be different between male and female mice. In the absence of sucrose, KKT administration decreased food intake only in male mice. However, while having access to a 30% sucrose solution, both BW and food intake was decreased by KKT administration in male and female mice; but sucrose intake was decreased in female mice alone. In addition, KKT administration decreased sucrose intake in oxytocin deficient lean mice, but not in the WT lean mice. The present study demonstrates that KKT ameliorates chronic inflammation, which is strongly associated with aging and obesity, and decreases food intake in male mice as well as sucrose intake in female mice; in an oxytocin receptor dependent manner.